1995
DOI: 10.1007/bf00191214
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-6 expression in normal and malignant prostate

Abstract: Bone morphogenetic proteins (BMPs) have multiple biologic functions, including bone formation and embryonic induction. One of these proteins, BMP-6, was reportedly expressed at high levels in human prostate cancers that had also metastasized to bone. This study investigated both BMP-6 mRNA and protein expression in normal and malignant rat and human prostate tissues. BMP-6 was detected in both rat normal prostate and in Dunning rat-prostate adenocarcinoma sublines. The levels of BMP-6 mRNA and protein were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…This result was in line with other findings, suggesting that BMP-6 might play a role in prostate cancer progression. 4 In contrast, we did not observe significant different noggin or sclerostin staining between high-and low-grade prostate cancers in our patient cohort. These results suggest that loss of BMPs inhibitors might not be a feature of high-grade prostate cancer.…”
Section: Bmp-6 Expression Is Upregulated In High-grade Prostate Cancercontrasting
confidence: 82%
See 1 more Smart Citation
“…This result was in line with other findings, suggesting that BMP-6 might play a role in prostate cancer progression. 4 In contrast, we did not observe significant different noggin or sclerostin staining between high-and low-grade prostate cancers in our patient cohort. These results suggest that loss of BMPs inhibitors might not be a feature of high-grade prostate cancer.…”
Section: Bmp-6 Expression Is Upregulated In High-grade Prostate Cancercontrasting
confidence: 82%
“…BMP-6 expression is higher in prostate cancer compared with benign prostate specimens as well as in high-grade compared with low-grade prostate cancers. 4,5 Its expression is high in primary prostate cancer of patients with metastases, whereas is low or undetectable in nonmetastatic prostate cancer and benign prostate specimens. 1,5 In addition, BMP-6 is also highly expressed in prostate cancer metastasized to bone.…”
mentioning
confidence: 99%
“…BMP-6 expression was detected in the prostate tissue of over 50% of patients with clinically defined metastatic prostate cancer, but was not detected in nonmetastatic or benign prostate samples. In another study focused on BMP-6 mRNA and protein expression, Barnes et al (24) observed that BMP-6 was produced by normal and neoplastic human prostate (radical prostatectomy specimens and human carcinoma cell lines DU145 and PC3). However, BMP-6 mRNA and protein expression was higher in prostate cancer compared with adjacent normal prostate, with higher-grade tumors (Gleason score of 6 or more) having greater BMP-6 immunostaining than the lower-grade tumors (Gleason score of 4 or less).…”
Section: Discussionmentioning
confidence: 99%
“…Although the expressions of several BMPs have been evaluated in prostate cancer, BMP-6 seems to be most consistently increased with increasing progression of prostate cancer (24,25). This observation, taken together with the knowledge that BMPs are pro-osteoblastic and induce bone formation, led us to hypothesize that up-regulation of BMP-6 expression in prostate cancer cells localized in the bone contributes to the development of osteoblastic lesions at prostate cancer metastatic sites in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Putative factors secreted by prostate cancer cells that affect osteoblast growth and differentiation could be involved in the progression of prostate cancer in bone (8). Several candidate factors including endothelin-1 (9), platelet-derived growth factor (10), and BMP-6 (11,12) have been identified. We previously identified a 45-kDa secreted isoform of ErbB-3 (p45-sErbB3, previously named MDA-BF-1) from the supernatants of bone marrow samples from men with prostate cancer and bone metastasis (13).…”
mentioning
confidence: 99%